Outcome of patients with stage IV high-risk Wilms tumour treated according to the SIOP2001 protocol: A report of the SIOP Renal Tumour Study Group. (March 2020) - Pasqualini, Claudia; Furtwängler, Rhoikos; van Tinteren, Harm; Teixeira, Roberto A.P.; Acha, Tomas; Howell, Lisa; Vujanic, Gordan; Godzinski, Jan; Melchior, Patrick; Smets, Anne M.; Coulomb-L'Hermine, Aurore; Brisse, Hervé; et al.
Abstract: Introduction: High-risk (HR) metastatic (stage IV) Wilms tumours (WTs) have a particular poor outcome. Methods: Here, we report the results of HR (diffuse anaplastic [DA] or blastemal type [BT]) stage IV WT treated patients according to the HR arm in the SIOP2001 prospective study. Results: From January 2002 to August 2014, 3559 patients with WT were included in the SIOP2001 trial. Among the 525 patients (15%) with metastatic WT, 74 (14%) had stage IV HR-WT. The median age at diagnosis was 5.5 years (range: 1.4–18.3). Thirty-four patients (47%) had BT-WT and 40 (53%) had DA-WT. Five-year event-free survival rates were 44 ± 17% and 28 ± 15% for BT-WT and DA-WT, respectively (p = 0.09). Five-year overall survival rates were 53 ± 17% and 29 ± 16% for BT-WT and DA-WT, respectively (p = 0.03). Metastatic complete response after preoperative treatment was significantly associated with outcome in univariate and multivariate analyses (hazards ratio = 0.3; p = 0.01). Postoperative radiotherapy of metastatic sites might also be beneficial. Forty-three of 74 patients experienced a relapse or progression predominantly in the lungs (80%). The median time to relapse/progression after diagnosis was 7.3 months (range: 1.6–33.3) and 4.9 months (range: 0.7–28.4) for BT-WT and DA-WT, respectively (p = 0.67). This is the first prospective evidence of inferior survival of stage IV BT-WT as compared with historical intermediate-risk WT. Survival of patients with stage IV DA-WT has not improved compared to the previous SIOP93-01 study. Conclusion: These results call for new treatment approaches for patients with HR stage IV WT. Highlights: Fourteen percent of patients with metastatic Wilms tumours (WT) have high-risk (HR) histology. Patients with metastatic WT with HR histology have a poor survival, despite intensive treatment. Metastatic complete response after preoperative treatment is associated with outcome.